Development and Implementation of Chemistry STEM-Based Module on Buffer Solution Material in Senior High School - Siregar, Litani; Silaban, Saronom (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
One of the issues class XI SMA Negeri 1 Purba students encounter is that the teaching materials still used aren't very diverse; they mostly consist of textbooks, which makes it difficult for students to comprehend the material in the textbook. The goal of this study is to create a STEM-based chemistry module that will enhance student learning outcomes and activities. Research and development (R&D) using the ADDIE development model is the research methodology applied. This STEM-based chemistry module scored on average 89.47% for content feasibility, 90.17% for presentation feasibility, 95.31% for STEM assessment, 82.69% for language feasibility, and 95.16% for graphics, placing it in the category of being "very feasible to use in learning." With average student pretest and posttest scores of 43.57 and 86.43 in small groups and 39.67 and 84.67 with an N-Gain score of 0.75 for student learning outcomes in large groups, the STEM-based chemistry module developed was deemed effective for improving student learning outcomes and student learning activities. The average value of all student learning activities was 77.4% with high criteria.